From immersion to collaborative embodiment: extending collective interactivity in built environments through human-scale audiovisual immersive technologies. Issue 3 (2nd July 2020) - Huang, Mincong; Chabot, Samuel; Krueger, Ted; Leitão, Carla; Braasch, Jonas
ABSTRACT: This paper discusses the use of human-scale immersive virtual environments as a platform for developing technologies for embodied digital interaction. We propose a three-body framework of spatial typologies in the realm of collaborative room-centered immersive systems that governs the relationship between the immersants, the hardware system of the environment, and the presented virtual environment. Through the lens of this framework, we present several use cases in the Collaborative-Research Augmented Immersive Virtual Environment Laboratory (CRAIVE-Lab) at Rensselaer Polytechnic Institute. Through the narratives of these use cases, it is argued that the proposed framework not only affords the design of interaction systems in room-centered virtual environments with spatial awareness, but also engenders new approaches to envision system design and its integration to the built environment. This framework intends to emphasize the significance of spatial thinking in expanding the creative potentials of body-driven interactive immersive systems.